CK2β-regulated signaling controls B cell differentiation and function - Quotti Tubi, Laura; Mandato, Elisa; Canovas Nunes, Sara; Arjomand, Arash; Zaffino, Fortunato; Manni, Sabrina; Casellato, Alessandro; Macaccaro, Paolo; Vitulo, Nicola; Zumerle, Sara; Filhol, Odile; Boldyreff, Brigitte; et al. (Frontiers in Immunology, 2023)
Serine-Threonine kinase CK2 supports malignant B-lymphocyte growth but its role in B-cell development and activation is largely unknown. Here, we describe the first B-cell specific knockout (KO) mouse model of the β regulatory subunit of CK2. CK2βKO mice present an increase in marginal zone (MZ) and a reduction in follicular B cells, suggesting a role for CK2 in the regulation of the B cell receptor (BCR) and NOTCH2 signaling pathways. Biochemical analyses demonstrate an increased activation of the NOTCH2 pathway in CK2βKO animals, which sustains MZ B-cell development. Transcriptomic analyses indicate alterations in biological processes involved in immune response and B-cell activation. Upon sheep red blood cells (SRBC) immunization CK2βKO mice exhibit enlarged germinal centers (GCs) but display a limited capacity to generate class-switched GC B cells and immunoglobulins. In vitro assays highlight that B cells lacking CK2β have an impaired signaling downstream of BCR, Toll-like receptor, CD40, and IL-4R all crucial for B-cell activation and antigen presenting efficiency. Somatic hypermutations analysis upon 4-Hydroxy-3-nitrophenylacetyl hapten conjugated to Chicken Gamma Globulin (NP-CGG) evidences a reduced NP-specific W33L mutation frequency in CK2βKO mice suggesting the importance of the β subunit in sustaining antibody affinity maturation. Lastly, since diffuse large B cell lymphoma (DLBCL) cells derive from GC or post-GC B cells and rely on CK2 for their survival, we sought to investigate the consequences of CK2 inhibition on B cell signaling in DLBCL cells. In line with the observations in our murine model, CK2 inactivation leads to signaling defects in pathways that are essential for malignant B-lymphocyte activation.